Research of Thin Aluminium Vacuum Coatings - Grigaliunas, V.; Kopustinskas, V.; Slapikas, K.; Margelevicius, J.; Andrulevicius, M. (Elektronika ir Elektrotechnika, 1997)
There was researched the influence of technological parameters for thin Al vacuum coatings on the polymeric surface having microoptical difraction relief. Composition of layers is shown by X - ray photoelectron spectroscopy analysis. Optical properties were studied by laser elipsometry analysis.